Molecular phylogenetics and definition of the Acrapex minima Janse group (Lepidoptera, Noctuidae, Apameini, Sesamiina) with the description of four new species from the Afrotropics - (:unkn) unknown (My University, 2017)
Five morphologically similar species of Acrapex Hampson (Lepidoptera, Noctuidae, Noctuinae, Apameini), from sub-Saharan Africa are reviewed, including four new species that are described: Acrapex mondogeneta Le Ru n. sp., A. mubale Le Ru n. sp., A. robe Le Ru n. sp. and A. rubona Le Ru n. sp. These five species belong to a species complex that we hereby define as the Acrapex minima group. Host plants of three species are recorded; Acrapex minima is recorded for the first time on a host plant, Digitaria natalensis Stent; A. mondogeneta on Hyparrhenia hirta (L.) Stapf and A. rubona on Imperata cylindrica (L.) P. Beauv. We also conducted molecular phylogenetics (using both Bayesian inference and maximum likelihood) and molecular species delimitation analyses (Poisson tree processes) on a six gene multi-marker dataset (four mitochondrial and two nuclear gene fragments; 4582 nucleotides in length) of 42 specimens and 22 species, including 23 specimens from the Acrapex minima group. The results of the corresponding analyses support the monophyly of the group and the species status of the newly described taxa.
Keywords: African Research